An improved Multipath Estimating Delay-Lock-Loop method based on Teager-Kaiser operator - Fa, Ji Yuan; Jie, Tian Lian; Yan, Sun Xi; Suqing, Yan; Kamarul Hawari, Ghazali; Khatuni, S. (Universiti Teknikal Malaysia Melaka (UTeM), 2018)
In the satellite navigation system, multipath signal propagation effect is the main source of errors to the receiver positioning accuracy. Research has been done on multipath mitigation algorithms but their implementation towards suboptimal or optimal receiver is in demand. One of the key multipath mitigation algorithms is Multipath Estimating DelayLock-Loop (MEDLL), which suffers from large amount of computational complexity, poor real-time performance and error accumulation. To overcome these drawbacks, an improved MEDLL algorithm is proposed here by combining it with the Teager-Kaiser (TK) algorithm and residual signal estimation -- named TK-MEDLL. Simulation results show that the algorithm can accurately estimate the number of multipath signal components, and improve the estimation accuracy of the signal parameters. Besides, TK-MEDLL can separate the multipath from the composite signal, restore the direct signal, and thus effectively suppress the multipath signal. Hence, the time delay estimation accuracy is improved by 0.015chip, whereas the estimation error is reduced by 5%. Overall, the algorithm reduces the computational complexity and improves the real-time performance of signal processing, which is of great significance for satellite communications.